Analysis of Muslim Students' Resilience in Coping with Prolonged Grief - Devy Probowati; Adi Atmoko; Muslihati; Widya Multisari; Salsabila Melati Sukma; Arilla Ainda Ubak; Fathia Majida Thoyyib (State Islamic University (UIN) Salatiga, 2026)
Resilience plays a crucial role in helping students cope with prolonged grief, as experiences of loss can negatively affect their psychological well-being. Therefore, this study aims to examine the effect of self-efficacy and self-esteem on students’ resilience in dealing with prolonged grief. This study employed a cross-sectional predictive design involving 346 students from Malang State University selected through purposive sampling. This study used three instruments measuring self-efficacy (X₁), self-esteem (X₂), and resilience (Y), all of which employed a Likert scale and were tested for validity and reliability. The reliability test showed α = .856 for the self-efficacy scale, α = .831 for the self-esteem scale, and α = .745 for the resilience scale. The results of the analysis after conducting validity tests and regression tests yielded the regression model Y=6.742+.412X₁+.283X₂+ε. The coefficients were β₁ (self-efficacy) = .412 (t = 4.568; p < .001) and β₂ (self-esteem) = .283 (t = 2.476; p = .014). The results indicate that self-efficacy and self-esteem significantly and positively predict resilience. This study contributes theoretically by supporting a positive psychology framework and providing recommendations for preventive interventions, although its cross-sectional design limits causal inference. Future research is encouraged to employ longitudinal or experimental designs and to include mediating or moderating variables such as social support, coping strategies, or personality factors to strengthen the explanatory model.